2021
DOI: 10.1002/jbm4.10497
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Calciprotein Particles in Adults Receiving Infliximab for Chronic Inflammatory Disease

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Another half of Ca 2+ and PO 4 3− ions and the remaining 5% fetuin-A are contained within the CPPs, 50 to 500 nm carbonate-hydroxyapatite particles adsorbing ambient serum proteins [ 1 , 2 , 3 , 4 , 5 ]. Both calciprotein monomers and CPPs act as physiological mineral buffering systems [ 8 , 80 ]; however, increased generation of CPPs and transition of amorphous CPP-P to crystalline CPP-S in the serum have been reported in patients with chronic kidney disease [ 17 , 18 ], cardiovascular disease [ 11 , 18 , 19 ], and autoimmune disorders [ 20 , 21 ], suggestive of mineral homeostasis disturbances in these clinical scenarios and demanding the development of specific therapeutic approaches. Our previous studies have shown that CPPs are internalised by ECs under flow and trigger calcium stress leading to their pro-inflammatory activation and even apoptosis [ 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another half of Ca 2+ and PO 4 3− ions and the remaining 5% fetuin-A are contained within the CPPs, 50 to 500 nm carbonate-hydroxyapatite particles adsorbing ambient serum proteins [ 1 , 2 , 3 , 4 , 5 ]. Both calciprotein monomers and CPPs act as physiological mineral buffering systems [ 8 , 80 ]; however, increased generation of CPPs and transition of amorphous CPP-P to crystalline CPP-S in the serum have been reported in patients with chronic kidney disease [ 17 , 18 ], cardiovascular disease [ 11 , 18 , 19 ], and autoimmune disorders [ 20 , 21 ], suggestive of mineral homeostasis disturbances in these clinical scenarios and demanding the development of specific therapeutic approaches. Our previous studies have shown that CPPs are internalised by ECs under flow and trigger calcium stress leading to their pro-inflammatory activation and even apoptosis [ 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with hyperphosphatemia (e.g., those with end-stage renal disease), a considerable proportion of primary amorphous CPPs transform into secondary crystallised CPPs, which instigate stronger cytokine release and indicate critical depletion of mineral buffering systems [ 15 , 16 ]. A number of reports documented that the serum of patients with chronic kidney disease [ 17 , 18 ], arterial hypertension [ 18 , 19 ], coronary artery disease [ 11 ], cerebrovascular disease [ 11 ], and autoimmune disorders [ 20 , 21 ] shows increased CPP generation that reflects uncurbed mineral stress in these clinical scenarios and emphasizes the need in the development of anti-CPP therapies. For the experiments, CPPs are routinely synthesised in vitro by the supersaturation of serum-supplemented cell culture medium with Ca 2+ and PO 4 3− ions [ 8 , 9 ], as artificially generated CPPs are similar to those isolated from calcified human tissues [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scores were weighted according to their contribution to the morbidity of the disease (maximal total score 64.5). To assess disease severity, the total score was then categorized as mild (<18), moderate (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), or severe (>38), as described previously [23]. End organ damage to the kidneys was defined as having chronic kidney disease (CKD) stage 3 or above (estimated GFR <60mL/min/1.73m 2 ) according to current Kidney Disease Improving Global Outcomes (KDIGO) Clinical Practice Guidelines for the Evaluation and Management of CKD, or previous renal transplantation.…”
Section: Study Design and Cohortmentioning
confidence: 99%
“…The existence of a "bone-vascular axis" has been suggested, implicating a complex interplay of the components regulating both systems [18], in which fetuin-A and CPP may function as mineral chaperones. High levels of circulating CPP have been reported in people with other chronic inflammatory disorders such as inflammatory bowel disease and inflammatory arthropathies [19], as well as in patients with end-stage kidney disease requiring dialysis therapy [20].…”
Section: Introductionmentioning
confidence: 99%